Quantum interference in heterogeneous superconducting-photonic circuits on a silicon chip - C. Schuck (Nature Portfolio, 2016)
Scaling photonic quantum information processing approaches remains challenging for integrated quantum optics. Here, Schuck et al.develop a hybrid superconducting-photonic circuit system to show how quantum interference and single-photon detectors can be combined in a scalable fashion on a silicon chip.